Pengalaman Praktis Mahasiswa MBKM dalam Penjualan Produk Franchise Es Teh di PT Anclev Inovasi Internasional - Elsa Damayanti; Maulidyah Indira Hasmarini (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
Tea is one of the most popular beverages among the Indonesian population. The high consumer demand for iced tea highlights the stable and growing market potential of this product. Responding to this opportunity, a business innovation was launched in the form of an iced tea business package aimed at enhancing the economic value of raw materials and empowering local communities. According to Indonesia’s Central Statistics Agency (BPS), national tea production reached 94.1 tons in 2021, showing a 20.3% increase from the previous year. The majority of tea production in Indonesia comes from West Java Province, which also has the largest tea plantation area in the country, reaching 86,832 hectares. This significant potential indicates that the availability of raw tea materials strongly supports the growth of tea-based beverage industries. Through this iced tea business program, it is expected that new business opportunities will emerge, increasing the economic value of local tea products and creating employment for surrounding communities. The business also holds considerable potential for sustainable development in light of the ongoing trend of ready-to-drink beverages.Keyword : Tea, Iced Tea, Beverage Industry, Value-Added Product, Business Opportunity, Local Economy